1970
DOI: 10.1021/i360033a009
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Stability of Fire-Retardant Rigid Polyurethane Foams from Phosphonopropionate Polyols

Abstract: gave a , of 0.002, whereas at A = 0 (pure ra-butylamine) the observed viscosity (6 cps) gave a , of 0.157. From the specific gravity of the amine (0.74) and the 1 to 1 complex (0.80), 0i for 2 to 1 and 3 to 1 mixtures gave theoretical values of 0.019 and 0.033, respectively, compared to observed values of 0.031 and 0.052. The viscosity lowering as calculated from Equation 2 is 32 cps (observed 60 cps) for the 2 to 1 mixture and 20 cps (observed 30 cps) for the 3 to 1 mixture. This deviation from observed value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Furthermore, with the same goal, carbohydrates were modified with an alkyl chain to improve the mixing with the PUF components [186]. The 36 synthesis of phosphorous-containing polyols with FR properties was achieved by the esterification of sorbitol and sucrose derivatives with dialkyl phosphonopropionate [187] or the treatment of propoxylated starch with polyphosphoric acid [188].…”
Section: Additivesmentioning
confidence: 99%
“…Furthermore, with the same goal, carbohydrates were modified with an alkyl chain to improve the mixing with the PUF components [186]. The 36 synthesis of phosphorous-containing polyols with FR properties was achieved by the esterification of sorbitol and sucrose derivatives with dialkyl phosphonopropionate [187] or the treatment of propoxylated starch with polyphosphoric acid [188].…”
Section: Additivesmentioning
confidence: 99%
“…23,24 It has been widely demonstrated that the most suitable reactive flame retardants for rigid polyurethane foams are mainly phosphoruscontaining polyols, such as 2,2′-((bis(hydroxymethyl) phosphoryl)methylazanediyl)diethanol, tris(dipropylene glycol)phosphonate, diethyl-N,N′-bis(2-hydroxyethyl)-aminomethylphosphonate, diethyl-N,N′-diethanolaminomethylphosphate, and morpholinophosphoryldimethanol. 20,25,26 Several new phosphorus-containing polyols, based on tetrakis-(hydroxymethyl)phosphonium chloride (THPC), have been used for rigid polyurethane foams, being introduced into the polyurethane main chain in the chain-extension step. 25,27−29 Moreover, the modified rigid polyurethane foams showed good flame resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In general, reactive-type flame retardants are mostly based on halogens and phosphorus. Recently, selected halogen-containing flame retardants have been banned because they have poor environmental profiles, along with some human health and toxicity effects. For this reason, there is a strong desire to develop effective nonhalogenated flame retardants with superior environmental profiles and the ability to react with foams and not leach into the environment. , It has been widely demonstrated that the most suitable reactive flame retardants for rigid polyurethane foams are mainly phosphorus-containing polyols, such as 2,2′-((bis(hydroxymethyl) phosphoryl)methylazanediyl)diethanol, tris(dipropylene glycol)phosphonate, diethyl- N , N ′-bis(2-hydroxyethyl)aminomethylphosphonate, diethyl- N , N ′-diethanolaminomethylphosphate, and morpholinophosphoryldimethanol. ,, Several new phosphorus-containing polyols, based on tetrakis(hydroxymethyl)phosphonium chloride (THPC), have been used for rigid polyurethane foams, being introduced into the polyurethane main chain in the chain-extension step. , Moreover, the modified rigid polyurethane foams showed good flame resistance. Usually, these phosphorus-containing polyols are used as chain extenders or reactive monomers for rigid polyurethane foams; however, they are rarely used for FPUF.…”
Section: Introductionmentioning
confidence: 99%
“…This is because RPUF synthesis is directly related to these fields. At present, the main methods for preparing RPUF in industrial production are the prepolymer method, semi-prepolymer method, and one-step method [ 42 ]. The prepolymer method reacts polyester or polyether with polyisocyanate to form prepolymer and then mixes the formed prepolymer with a catalyst, foaming agent, and other preparation materials to form RPUF.…”
Section: Resultsmentioning
confidence: 99%